CGIAR Open and FAIR Data Assets Policy - CGIAR System Management Office (2021)
Approved by the System Management Board with effect from 16 April 2021 (Decision reference SB/M19/EDP3). This Policy supersedes and replaces in its entirety the 2013 Open Access and Data Management Policy. It addresses funder and publisher requirements, the recommendations of a 2018 external assessment undertaken pursuant to the recommendation of the then CGIAR Independent Evaluation Arrangement and responds to a 2020 Data Management Maturity Assessment.